Are Argumentation Skills Can Describe Understanding Concepts? - Fadilah Rohmah Yulianing; Suyono Suyono; Sukarmin Sukarmin; Farrizky Noor Thoriq; Nurul Auliya; Rezi Ulya Fauziah (Indonesia Emerging Literacy Education, 2023)
Objective: Based on the several aspects, one aspect is quite important in the process of learning science, namely communicating. Argumentation is one of communication skills. Are argumentation can describe understanding concepts? Method: This study uses a literature review method from thirteen articles. Results: Argumentation skills can describe understanding concepts. Interpretation of the correlation coefficient shows that argumentation skills strongly correlate with understanding concepts. It is because argumentation skills positively correlate with critical thinking and logic skills. Argumentation skills can improve students' critical thinking level and logical skills in the thinking process. Everyone has good argumentation skills if has good critical thinking and good logic skills. Novelty: Argumentation skills are one of the communication skills that improve understanding of concepts. Argumentation skills are moderators for high-order thinking skills. It can occur because the components of argumentation skills are claim, evidence, and reasoning. Someone can meet all the argumentation skills components with good thinking.